2016
DOI: 10.1007/s00410-016-1248-6
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur isotope and trace element systematics of zoned pyrite crystals from the El Indio Au–Cu–Ag deposit, Chile

Abstract: crystals in high-temperature feeder zones range from −3.19 to 1.88 ‰ (±0.5 ‰), consistent with sublimation directly from a high-temperature magmatic vapor phase. Late pyrite crystals are distinctly more enriched in δ 34 S than early pyrite (δ 34 S = 0.05-4.77 ‰, ±0.5 ‰), as a consequence of deposition from a liquid phase at lower temperatures. It is unclear whether the late pyrite was deposited from a small volume of liquid condensate, or a larger volume of hydrothermal fluid. Both types of pyrite exhibit intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Studies in geothermal systems and epithermal Au-Ag deposits have shown that pyrite can display a large variety of textures, including brecciated, colloform, porous, fibrous and inclusionrich textures (e.g., Deditius et al, 2009a, b;Franchini et al, 2015;Tanner et al, 2016;Kouhestani et al, 2017). In the CPGS, pyrite grains show several of these textures and morphologies, including porous and inclusion-rich zones, and brecciated subhedral to euhedral pyrite grains (Figs.…”
Section: Interpretation Of Pyrite and Gangue Minerals Texturesmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies in geothermal systems and epithermal Au-Ag deposits have shown that pyrite can display a large variety of textures, including brecciated, colloform, porous, fibrous and inclusionrich textures (e.g., Deditius et al, 2009a, b;Franchini et al, 2015;Tanner et al, 2016;Kouhestani et al, 2017). In the CPGS, pyrite grains show several of these textures and morphologies, including porous and inclusion-rich zones, and brecciated subhedral to euhedral pyrite grains (Figs.…”
Section: Interpretation Of Pyrite and Gangue Minerals Texturesmentioning
confidence: 99%
“…Pyrite is a ubiquitous and abundant sulfide in ore deposits, and several geochemical studies have highlighted its role as a major Au-bearing phase and scavenger of metals and metalloids. Most notably, pyrite has been used as a geochemical tracer in a wide variety of hydrothermal ore deposits including orogenic, sediment-hosted Carlin-type, epithermal Au deposits, volcanic-massive sulfide (VMS), porphyry Cu and iron-oxide apatite (IOA) deposits (Cook and Chryssoulis, 1990;Fleet et al, 1993;Huston et al, 1995;Simon et al, 1999;Vaughan and Kyin, 2004;Reich et al, 2005Reich et al, , 2006Reich et al, , 2013Reich et al, , 2016Large et al, 2009Large et al, , 2014Cook et al, 2009a;Deditius et al, 2009aDeditius et al, ,b, 2011Deditius et al, , 2014Koglin et al, 2010;Franchini et al, 2015;Gregory et al, 2015a;Deditius and Reich, 2016;Tanner et al, 2016;Keith et al, 2018). These studies have provided not only a better understanding of metal speciation and partitioning during mineral precipitation, but also have illustrated how physico-chemical processes drive changes in trace element distributions during superimposed events, including hydrothermal alteration, metamorphism and/or associated deformation (Large et al, 2007;Cook et al, 2009a;Thomas et al, 2011;Reich et al, 2013;Deditius et al, 2014;Steadman et al, 2015;Meffre et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations